Debriefing to Improve Student Ability to Assess and Plan for the Care of Persons With Disability. Issue 6 (December 2017) - Takeda, Mikiko Y.; Smith, Mark J.; Cone, Catherine J.
Abstract : Introduction: Although recent literature suggests that students should be trained in the care of persons with disability (PWDs) as a form of cultural sensitivity (CS), healthcare professionals may receive limited experience during their formal training. After pharmacy students in 2 previous years of testing failed to adequately assess and plan for the care of a standardized patient's chief complaint and disability in an Objective Structured Clinical Examination (OSCE), the investigators added debriefing to the OSCE to determine if it would improve student's ability to assess and plan for the care of PWD. Methods: Two sequentially enrolled second-year pharmacy school student cohorts participated in this study (control n = 90; intervention n = 82). During the OSCE, students interviewed and examined a standardized patient with a simulated physical disability and other chronic disease states. Students were then instructed to develop a care plan considering the patient's disability and other disease states. The intervention cohort received debriefing; the control did not. Students documented the care plan in a subjective, objective, assessment, and plan (SOAP) note. Investigators assessed SOAP note score (general ability of students to write a SOAP note) and CS score (specific ability to care for PWD) to determine the effectiveness of the debriefing. Results: The intervention group showed a significantly higher percent mean CS score than the control group (93.6% ± 19% and 61.1% ± 30.7%, respectively, P < 0.001), translating to a mean of 56.2/60 points earned for the intervention group and 36.7/60 points earned for the control group. Scores ranged from 0 to 60 points for both intervention and control groups. Students in the intervention group had an absolute improvement in pass rates (those students scoring ≥70% on the OSCE) of 59.4% with 92.7% of the students passing in the intervention group versus 33.3% of the students passing in the control group ( P < 0.001). The overall SOAP note scores were no different between the 2 cohorts ( P = 0.353). Conclusions: Debriefing added to an OSCE improved students' performance in developing care plans for disabled patients. Ideally, longitudinal studies should be completed to determine if these skills transfer from debriefings to clinical practice. Development of effective training and assessment methods is essential for students to obtain adequate skills and knowledge to care for persons with disabilities.